1994
DOI: 10.1007/bf00348207
|View full text |Cite
|
Sign up to set email alerts
|

Doppler analysis of hepatic blood flow predicts liver dysfunction after major hepatectomy

Abstract: In 17 consecutive patients who underwent major hepatic resection, 9 of whom with combined resection of the gastrointestinal tract or the pancreatic head (or both), postoperative hepatic blood flow was investigated. In this study, the patients were classified into two groups according to their postoperative serum total bilirubin level: Group A comprised 7 patients with the level higher than 7 mg/dl for more than 1 week postoperatively, and group B comprised 10 patients who did not meet this criterion. For 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
0
33
0
4
Order By: Relevance
“…Following hepatectomy, the loss of liver functional mass and vascular capacity result in a marked increase in hepatic artery resistance and an increase in portal vein pressure [71]. Excessive portal vein pressure may result in microcirculatory collapse, sinusoidal endothelial damage, Kupffer cell injury and subsequent lack of hepatocyte regeneration up to liver atrophy [72].…”
Section: Pathogenesismentioning
confidence: 99%
“…Following hepatectomy, the loss of liver functional mass and vascular capacity result in a marked increase in hepatic artery resistance and an increase in portal vein pressure [71]. Excessive portal vein pressure may result in microcirculatory collapse, sinusoidal endothelial damage, Kupffer cell injury and subsequent lack of hepatocyte regeneration up to liver atrophy [72].…”
Section: Pathogenesismentioning
confidence: 99%
“…As a second mechanism, hemodynamic changes with an upregulation of portal flow are known to regulate liver regeneration and hypertrophy. Several studies have shown that the degree of hypertrophy is directly correlated with the increase in portal flow [14,15,16,17,18,19,20], whereas the rate of hypertrophy and liver regeneration are directly related to the degree of atrophy of the occluded liver lobe without a change in the total liver volume [21,22,23]. Besides the increase in portal vein flow, different authors described an inverse significant reduction in arterial flow, which has been described as hepatic arterial buffer response (HABR) [20,21,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Zero calibration was confirmed when the blood flow is important for preventing liver failure fol-probes were excised. Data were recorded on a polygraph system lowing a liver resection [3]. Feeding is one of the most (A601, Nihon Koden, Tokyo, Japan) and a direct writing recorder (TI-250, Tokai Irika, Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%